Evaluation of Apical Sealing Ability of Four Endodontic Sealers: An In vitro Study - Sourabh Ramesh Joshi; S. Sruthi; Viddyasagar Prabhakar Mopagar; Neeta Surendra Padmawar; Gowri Swaminatham Pendyala (Journal of International Clinical Dental Research Organization)
Introduction: Three-dimensional filling of the root canal system is widely recognized as crucial for the success of endodontic treatment, the main reason for endodontic failure persists as microleakage that happens between the filling material in the root canal and the walls of the canal. A significant factor contributing to microleakage subsequent to endodontic procedures is the leakage of blood from the apex of the tooth. Therefore, it is imperative to provide a good apical seal to prevent reinfection by spread of microbial toxins. Root canal sealers combined with core obturating material are aimed to create a fluid tight apical seal. Aim: To evaluate the sealing ability of MTA Fillapex, CeraSeal, CeraSeal-B and AH Plus. Objectives: To evaluate and compare the sealing ability of MTA Fillapex, CeraSeal, CeraSeal-B and AH Plus. Material and Methods: Sixty freshly extracted single rooted sound human teeth were selected based on inclusion and exclusion criteria. The samples were divided by simple random sampling method into 4 groups with 15 teeth in each group namely Group A: MTA Fillapex, Group B: CeraSeal, Group C: CeraSeal B, Group D: AH Plus. The teeth sealed with respective sealers were obturated using thermoplasticized gutta percha technique. The samples were stored at 37°C and 100% humidity to assure the setting of the sealer. The samples were immersed in 2% methylene blue solution for 7 days. The linear measurement of dye penetration from the root apex to the greatest coronal extent was evaluated under stereomicroscope at 20 X magnification. Results: After complete statistical evaluation, it was inferred that the intergroup comparison showed MTA Fillapex, CeraSeal, AH Plus to have statistically non-significant mean difference (p>0.05). Cera Seal B had highest mean dye penetration (2.59 ± 1.11) and the difference was statistically significant (p<0.05). Conclusion: Maximum dye penetration was seen in CeraSeal B, showing it had the lowest sealing ability. that CeraSeal had slightly higher sealing ability as compared to AH Plus and MTA Fillapex, although their difference was statistically non-significant.